2002
DOI: 10.1002/1521-3773(20021202)41:23<4489::aid-anie4489>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Solid-Phase Synthesis of a Complex, Branched N-Glycan Hexasaccharide: Use of a Novel Linker and Temporary-Protecting-Group Pattern

Abstract: Oligosaccharides are known to be important molecules in various biological processes; therefore, they have gained increasing interest in recent years. [1] However, in contrast to oligopeptides [2] and oligonucleotides [3] which are routinely constructed on automated synthesizers employing standardized building blocks and polymer supports, no generally applied synthetic methodology has yet appeared for the solidphase synthesis of complex oligosaccharides. [4] Success in this challenging task would provide sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 15 publications
0
41
0
Order By: Relevance
“…It is important to note that different resin loadings could be achieved by employing different molar quantities of (4-trityloxymethyl-phenyl)-methanol. However, it was found that a loading of approximately 0.15 mmol g −1 resin gives optimal glycosylation results and further increases in loading led to decreases in coupling efficiencies 27,28…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that different resin loadings could be achieved by employing different molar quantities of (4-trityloxymethyl-phenyl)-methanol. However, it was found that a loading of approximately 0.15 mmol g −1 resin gives optimal glycosylation results and further increases in loading led to decreases in coupling efficiencies 27,28…”
Section: Resultsmentioning
confidence: 99%
“…27-31 Schmidt and coworkers have achieved solid-phase synthesis of a small library of N-glycan (Scheme 16.15). [32][33][34] They used the hydroxymethylbenzyl benzoate linker attached to the Merrifield resin. Glycosylation on the resin was successfully performed using the glycosyl trichloroacetimidates, 35 Later on, they have also investigated the orthogonality of the ester protecting groups at the vicinal hydroxyls on solid supports, that is, Fmoc, phenoxyacetyl (PA), allyloxycarbonyl (Alloc), and levulinoyl groups (Lev), at the C3 and C4 diols of the glucosamine as the model case.…”
Section: Solid-phase Synthesis Of Complex Oligosaccharidesmentioning
confidence: 99%
“…38 have stimulated many synthetic developments. 41,4451 Another representative example is the globoside family of glycosphingolipids (Figure 1B; Neu, N -acetylneuraminic acid; Fuc, fucose), whose members present a broad range of significant biological roles as glycan biomarkers. For example, Gb3 is overexpressed in colorectal adenoma cells, 52 in Burkitt’s lymphoma cells, 53 and in breast and ovarian cancer.…”
Section: Introduction: Carbohydrates Oligosaccharides Biological Romentioning
confidence: 99%